The Hematopoietic Niche in Myeloproliferative Neoplasms - Annette H. Schmitt-Graeff; Roland Nitschke; Robert Zeiser (Mediators of Inflammation)
Specialized microanatomical areas of the bone marrow provide the signals that are mandatory for the maintenance and regulation of hematopoietic stem cells (HSCs) and progenitor cells. A complex microenvironment adjacent to the marrow vasculature (vascular niche) and close to the endosteum (endosteal niche) harbors multiple cell types including mesenchymal stromal cells and their derivatives such as CAR cells expressing high levels of chemokines C-X-C motif ligand 12 and early osteoblastic lineage cells, endothelial cells, and megakaryocytes. The characterization of the cellular and molecular networks operating in the HSC niche has opened new perspectives for the understanding of the bidirectional cross-talk between HSCs and stromal cell populations in normal and malignant conditions. A structural and functional remodeling of the niche may contribute to the development of myeloproliferative neoplasms (MPN). Malignant HSCs may alter the function and survival of MSCs that do not belong to the neoplastic clone. For example, a regression of nestin+ MSCs by apoptosis has been attributed to neuroglial damage in MPN. Nonneoplastic MSCs in turn can promote aggressiveness and drug resistance of malignant cells. In the future, strategies to counteract the pathological interaction between the niche and neoplastic HSCs may offer additional treatment strategies for MPN patients.